OPTIMISM, ALTRUISM AND RELIGIOUS COPING POST COVID-19 PANDEMIC: Bahasa Inggris - Herawati, Netty; Rohmah, Nailur; Bulut, Sefa (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2023)
Post Covid-19 conditions still leave trauma for some people, especially those who have experienced pain and even loss of family members. The ability to deal with trauma is the ability to adapt to conditions. The aim of this study was to find out how optimism and altruism influence post-pandemic religious coping. The subjects of this study amounted to 820 men and women, aged 23-58 years old. The brief RCOPE, LOT-R and the altruism scale are instruments to find out the level of religious coping, optimism and altruism respectively. Based on the parametric-statistical analysis with product moment correlation from Pearson, there was a correlation between optimism and religious coping and there was also a correlation between altruism and religious coping. Based on multiple regression analysis, this study showed that both variables can simultaneously be predictors of religious coping.